The Delivery of α1-Antitrypsin Therapy Through Transepidermal Route: Worthwhile to Explore - Tumpara, Srinu; Martinez-Delgado, Beatriz; Gomez-Mariano, Gema; Liu, Bin; DeLuca, David S.; Korenbaum, Elena; Jonigk, Danny; Jugert, Frank; Wurm, Florian M.; Wurm, Maria J.; Welte, Tobias; Janciauskiene, Sabina (Frontiers in Pharmacology, 2020)
Human α1-antitrypsin (AAT) is an abundant acute phase glycoprotein expressing anti-protease and immunomodulatory activities, and is used as a biopharmaceutical to treat patients with inherited AAT deficiency. The pleiotropic properties of AAT provide a rationale for using this therapy outside of inherited AAT deficiency. Therapy with AAT is administrated intravenously, yet the alternative routes are being considered. To examine the putative transepidermal application of AAT we used epiCS®, the 3D human epidermis equivalents reconstructed from human primary epidermal keratinocytes. We topically applied various concentrations of AAT protein with a constant volume of 50 µl, prepared in Hank’s balance solution, HBSS, to epiCS cultured under bascondition or when culture medium supplemented with 100 µg/ml of a combined bacterial lipopolysaccharide (LPS) and peptidoglycan (PGN) mixture. AAT freely diffused across epidermis layers in a concentration and time-dependent manner. Within 18 h topically provided 0.2 mg AAT penetrated well the stratum corneum and localizes within the keratinocytes. The treatments with AAT did not induce obvious morphological changes and damages in keratinocyte layers. As expected, LPS/PGN triggered a strong pro-inflammatory activation of epiCS. AAT exhibited a limited capacity to neutralize the effect of LPS/PGN, but more importantly, it lowered expression of IL-18 and IL-8, and preserved levels of filaggrin, a key protein for maintaining the epidermal barrier integrity. Our findings suggest that the transepidermal route for delivering AAT is worthwhile to explore further. If successful, this approach may offer an easy-to-use therapy with AAT for skin inflammatory diseases.